Assertive Illocutionary Acts of Zakir Naik in General Lecture on Similarities between Christianity and Islam - Febriant Argadie Kusumah; Deli Nirmala (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2021)
This study analyzes the assertive illocutionary speech acts used by the Indian preacher, Zakir Naik in interfaith studies. This study identifies the types of assertive illocutionary speech acts used by Zakir Naik, then analyzes the findings of assertive illocutionary speech acts based on the felicity conditions and IFIDs (Illocutionary Force Indicating Devices). The author uses a qualitative descriptive research method. In analyzing the data findings, the writer uses speech act theory. The findings of this study are that there are three kinds of assertive illocutionary speech acts, namely: quoting, stating and informing which are used by Zakir Naik in his religious lectures and quoting techniques tend to be used more by lecturers.Keywords: speech act; assertive illocutionary act; Zakir Naik